Ultrasonic creep detection system for landslide monitoring - Diaz, Josef Karlo S. (2008)
Landslide monitoring is the process of observing factors and conditions that may lead to landslide. Several techniques are available for landslide monitoring applications. Among them are vibrating wire piezometers to measure groundwater levels and inclinometers, tilt meters and extensometers to monitor slope movement. Wireless sensor networks provide easy deployment of a dense array of sensor nodes over a large area. A wide selection of sensor boards allow these nodes to measure ambient conditions, like temperature, light and sound, among other things. A variety of localization techniques provide these nodes knowledge of their absolute and relative positions, with a high degree of accuracy. This research aims to bring the advantages of wireless sensor networks to landslide monitoring applications. It proposes a creep detection system that will use ultrasonic waves and detect all two-dimensional movements with sub-millimeter accuracy. It will employ peak detection and correlation to detect waveform shift. It will measure ambient temperature and relative humidity, and solve for the speed of sound. Then it will produce vector information (magnitude and angle) of the detected physical displacement. The system detected all two-dimensional movements and achieved sub-millimeter accuracy in its readings. The mean magnitude error is 0.092mm and mean angle is 2.550 degrees.
"March 2008."
Thesis (M.S. Electrical Engineering)--University of the Philippines Diliman.
Keywords: Wireless sensor networks -- Landslide -- Monitoring; Landslide hazard analysis; Global Positioning System